(untitled) (REMUNOM, 2024)
The theme of the Environment has been increasingly gaining ground in society, so that public and private institutions have implemented sustainable actions to achieve strategic objectives. This article aimed to analyze the feasibility of adhesion of the Federal University of Pará (UFPA) to the Public Administration Environmental Agenda (A3P) through a structured questionnaire applied in three sectors of the institution, chosen due to its relevance to the topic, addressing the five thematic axes proposed by A3P and carrying out a diagnosis of the feasibility of joining A3P, verifying how environmental issues are included in UFPA. It was identified that UFPA has been advancing in the implementation of several actions to adhere to the A3P, but several projects still need to be developed to consolidate this adherence and guarantee compliance with current standards regarding sustainability.